The Effect of Hatha Yoga Therapy on the Blood Pressure of Primary Hypertension Patients of Productive Age - Tamba, Darwin; Dharmajaya, Ridha; Sitohang, Nur Asnah (Jurnal Keperawatan Soedirman, 2021)
Untreated hypertension can lead to serious complications. One of the nonpharmacological therapies for treating hypertension is hatha yoga. The study aimed to determine the effect of hatha yoga therapy on the blood pressure of those of productive age among primary hypertension patients. The research type was a quasi-experiment with pre-posttest with control group design. The number of study samples was 64 respondents consisting of 32 respondents in the intervention group (who were given 35 minutes of hatha yoga therapy and Amlodipine 5mg/day for 4 weeks) and 32 respondents in the control group who received Amlodipine 5mg/day for 4 weeks. The data analysis used the dependent test (paired t test). The results showed that the mean of systolic and diastolic of blood pressure before the therapy in primary hypertension patients in the intervention group was 161.84 / 93.25 mmHg, while in the control group it was 161.66 / 93.37 mmHg. The mean of the systolic and diastolic blood pressure after therapy in the primary hypertensive patients in the intervention group was 122.87 / 71.69 mmHg, and in the control group it was 127.66 / 73.13 mmHg. The statistical tests using paired t-test showed that the p value was <? = 0.05. In conclusion, hatha yoga therapy has the effect of lowering blood pressure for those of productive age among primary hypertension patients.